Supervision of the Distribution of Subsidized Fuel Oil (BBM) Type Solar (Biosolar) in Padang City - Hariqah, Puja; Rahmadani Yusran (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to analyze the supervision of the distribution of subsidized diesel fuel (biosolar) in Padang City and the inhibiting factors in the supervision. This research uses descriptive analysis method with qualitative approach. Data were collected through observation, interviews, and documentation studies from various informants related to the supervision of the distribution of subsidized diesel fuel. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of this study indicate that supervision of the distribution of subsidized diesel fuel oil in Padang City is carried out in the form of issuing circulars, forming supervisory task forces, and conducting monitoring and counseling. However, the supervision of the distribution of subsidized diesel fuel is faced with problems, namely the misuse of subsidized fuel oil in Padang city, the supervision task force and coordination between sectors have not run optimally, there is no direct monitoring in the field conducted by the Regional Government. The suggestion from this research is the need for local government coordination with the central government to encourage clearer policies related to the authority and role of the Provincial and Regency or City Governments in supervising the distribution of subsidized diesel fuel.